The Measurement of Residents’ Perceptions on the Usage of Local Cuisine for Tourism - Şengül, Serkan; Türkay, Oğuz; Yılmaz, Özer (Anais Brasileiros de Estudos Turísticos, 2022)
Although the role of local cuisines in tourism development is clearly recognized, the number of studies measuring local people’s approaches to the presentation of local cuisines to tourists is limited. The aim of this study is to develop a scale identifying the perspectives of the indigenous dwellers living in tourism regions for the use of local cuisine as tourism products. The study focuses on the perceptions of the indigenous dwellers on the development of tourism in the region and use of local elements for tourism purposes. In this manner, data were collected from local authorities and people living in Mudurnu/Bolu/Turkey by using semi-structured interviews and questionnaire technique. The scale validity was tested by subjecting data to statistical analysis. The findings have proved that the scale, which was formed by 24 of 25 obtained statements as a result of literature review and semi-structured interviews, makes a valid measurement of the use of local food for tourism purposes. The view of the indigenous dwellers emerges within the scope of culture, economy, promotion, protection, employment and degeneration of cuisine culture. It is of great importance for the sustainability of gastronomic tourism to identify the view of the indigenous dwellers to the use of local food in tourism destinations. This study has contributed to the literature about measuring indigenous dwellers’ view on presentation of local cuisine.